The Role Of Islamic Banks In Halal Tourism Development : Evidence From Central Java Indonesia - Kuat Ismanto; Fachrurazi; Muhammad Aunurrochim Mas'ad (Department of Management, Faculty of Islamic Economics and Business, Univeritas Islam Negeri Walisongo Semarang, 2024)
Non-Indexed Publication